Analytic properties of Ohno function - Kamano, Ken; Onozuka, Tomokazu (MATHEMATICA SCANDINAVICA, 2021)
Ohno’s relation is a well-known relation on the field of the multiple zeta values and has an interpolation to complex function. In this paper, we call its complex function Ohno function and study it. We consider the region of absolute convergence, give some new expressions, and show new relations of the function. We also give a direct proof of the interpolation of Ohno’s relation.